Características metrológicas de las enzimas involucradas en el metabolismo de la glucosa en el uso del diagnóstico clínico (2023)
In the clinical field, metrology is crucial to ensure the quality and reliability of results in clinical analyses, especially when measuring concentrations in biological samples and knowing the biochemical activity of enzymes in patients, in order to determine reliable treatments, follow-ups, and diagnoses. The lack of standardization, traceability, quality problems, and personnel's capacity to perform these assays with precision and accuracy are some of the problems that metrology must overcome.